Penerapan Prinsip Desain pada Kemasan Oleh-Oleh Makanan Bandung - Aulia, Rahmiati; Swasty, Wirania; Eka Nastiti, Nisa (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
A souvenir can be interpreted as a reminder of an experience from a particular tourist trip. From all kind of souvenirs, food is a type of souvenir that tourist favours so much as a local identity for specific places. This research aims to document and map souvenir packaging for Bandung’s special food that existed between 1930 to 2020 and evaluate the application of design principles while also evaluating the application of design principles such as balance, unity/harmony, emphasis,contrast, scale/proportion/alignment, patterns/repetition, and movement/rhythm/flow on that packaging. The research also records the design elements used in the packaging, identifying those that are present and those that are not. These elements include typography/typeface, images/illustrations, color, graphic forms, layout, branding, and logos. This research uses qualitative methods by using Nvivo calculation. The result of this research is expected to know how far the application of principal design for Bandung’s special food between 1930 to 2020 was used. The packaging is classified into several criteria: legendary and well-established Bandung brands, brands that have entered modern retail (souvenir shops), authentic local cuisine brands, and newly established brands (startups). After filtering, nine brands representing different product categories were selected according to these criteria. The study aims to offer insights that contribute to the main objective: creating value in SME product labeling and packaging in Bandung. The findings of this paper can also be used for further research involving samples from various case studies.